Diagnostic criteria in Pai syndrome: results of a case series and a literature review. Issue 3 (March 2019) - Morice, A.; Galliani, E.; Amiel, J.; Rachwalski, M.; Neiva, C.; Thauvin-Robinet, C.; Vazquez, M.-P.; Picard, A.; Kadlub, N.
Abstract: Pai syndrome was originally described as the association of a midline cleft lip, midline facial polyps, and lipoma of the central nervous system. However, only a few patients present with the full triad, and most exhibit a wide spectrum of phenotypic variability. The aim of this study was to phenotypically delineate Pai syndrome and to propose new criteria to facilitate a clinical diagnosis in the future. The study cohort consisted of seven case patients and an additional 60 cases diagnosed with Pai syndrome identified in a literature review. Only 23 of 67 patients presented the full triad as historically described by Pai et al. (1987). A congenital facial midline skin mass was always encountered, particularly affecting the nasal structures (60/67). A midline facial cleft was reported in 45 of 67 patients and a pericallosal lipoma in 42 of 67 patients. The proposed definition of Pai syndrome is the association of (1) a congenital nasal and/or mediofrontal skin mass and/or a mid-anterior alveolar process polyp as a mandatory criterion, and at least one of the following criteria: (2) midline cleft lip and/or midline alveolar cleft, and/or (3) a pericallosal lipoma or interhemispheric lipoma in the case of corpus callosum dysgenesis.